A busca da felicidade como efetividade do Direito - Farias, Cyntia Mirella da Costa (2017)
Social advances and, above all, catastrophes in most distinct areas of human life have made man desire and ferociously seek his right to be happy. The aim of this paper is to classify the framework of the right to the pursuit of happiness and to prove its performance in Western legal order effectiveness . Philosophy was resorted and we observed that happiness is changeable, indeterminate, multifaceted and multicultural, and its pursuit is timeless. We verified the individual presence of the pursuit of happiness in each generation of fundamental rights struggle. The dynamics of the pursuit of happiness for the fulfillment of satisfaction occurs through the phenomenon of Dynamogenesis. Having proven the effectiveness of the Law by virtue of the pursuit of happiness we reserve the third and last chapter to understand how it occurs in the international and national scope. The United Nations has elevated the Happiness status to sustainable development goal. The Brazilian Constitutions, although it does not expressly express the right to the pursuit of happiness as it does in other legal systems, is validating this goal. As a conclusion, we brought all the cases in the Supreme Court and the Superior Court of Justice showing the right to the pursuit of happiness in their grounds of approval or rejection. We distinguished the minimum existence of human dignity and its relationship with happiness and we perceived that our stufy subject has a hybrid characteristic because it is attainable (so it is not utopian), but always longed for (so its not finished). The pursuit of happiness is the vivification of law, giving it meaning, strength and direction, so that its juridical nature is a vector